Ecotoxicity of losartan potassium in aquatic organisms of different trophic levels - Reque, Regiane; Carneiro, Rhaissa Dayane; Yamamoto, Flávia Yoshie; Ramsdorf, Wanessa Algarte; Martins, Lucia Regina; Guiloski, Izonete Cristina; de Freitas, Adriane Martins (Elsevier, 2021)
The intensive use of the antihypertensive losartan potassium (LOS) has culminated in its high occurrence in aquatic environments. However, insufficient studies had investigated its effects in non-target organisms. In this study, ecotoxicity of LOS was assessed in aquatic organisms from distinct trophic levels (Desmodesmus subspicatus, Daphnia magna, and Astyanax altiparanae). Genotoxicity was assessed by the comet assay in D. magna and A. altiparanae, and biochemical biomarkers for the fish. LOS was more toxic to D. subspicatus (EC50(72h) = 27.93 mg L−1) than D. magna (EC50 = 303.69 mg L−1). Subsequently, this drug showed to induce more DNA damage in D. magna than A. altiparanae, when exposed to 2.5 mg L−1. No significant stress responses were observed by the fish biomarkers, suggesting that higher trophic levels organisms are more tolerant to LOS toxicity. LOS showed relatively low toxic potential for a short period of exposure, but with different patterns of toxicity for the organisms from distinct trophic levels, contributing to further risk assessment of LOS.
Keywords: Antihypertensive drugs; Aquatic organisms; Biochemical biomarkers; Distinct trophic levels; Genotoxicity